Customer Satisfaction Linking Product Diversity and Service Quality to Repurchase Intention in Retail - Ramadhon, Luthfi; Winadi Prasetyoning Tyas, Ari Anggarani (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study investigates the influence of product diversity and service quality on repurchase intention in a modern retail context, with customer satisfaction positioned as an intervening construct. An explanatory quantitative approach was employed, drawing on data collected from 110 consumers of Superindo Daan Mogot through a structured questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the variables. The results indicate that product diversity and service quality do not exert significant direct effects on repurchase intention. Instead, both variables demonstrate a significant influence on customer satisfaction, which in turn shows a strong positive effect on repurchase intention. These findings suggest that repeat purchasing behavior is shaped less by isolated retail attributes and more by consumers’ evaluative judgments of their overall shopping experience. Customer satisfaction therefore operates as a key explanatory mechanism through which retail performance attributes are internalized into behavioral intention. This study shows that, in a relatively standardized supermarket environment, product diversity and service quality shape repurchase intention primarily through customer satisfaction rather than through direct effects. From a practical perspective, the findings suggest that retail strategies should focus on integrating product assortment quality and service delivery in ways that consistently enhance customer satisfaction and support long-term customer retention.